Numerical continued fraction interpolation - Celis, Oliver Salazar; Celis, Oliver Salazar (Institute of Mathematics, NAS of Ukraine, 2024)
UDC 517.524 We show that highly accurate approximations can often be obtained by constructing Thiele interpolating continued fractions by a Greedy selection of the interpolation points together with an early termination condition. The obtained results are comparable with the outcome of state-of-the-art rational interpolation techniques based on the barycentric form.